ANALISIS WACANA TEKSTUAL DAN KONTEKSTUAL DALAM NASKAH DRAMA SENJA DENGAN DUA KELELAWAR KARYA KIRDJOMULYO DAN RELEVANSINYA SEBAGAI BAHAN AJAR DI SEKOLAH MENENGAH ATAS - Nuryani, Nina; Setiawan, Budhi; Saddhono, Kundharu (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The purpose of this study is to describe (1) the form of textual analysis in the drama script Senja dengan Dua Kelelawar by Kirdjomulyo; (2) the form of contextual analysis in the drama script Senja dengan  Dua Kelelawar by Kirdjomulyo; and (3) the relevance of the results of this study as teaching materials for Indonesian language learning in senior high schools. This research is a qualitative research with the main data source as the drama script Senja dengan Dua Kelelawar by Kirdjomulyo. Data validity test used is theory triangulation. The sampling technique of this study used purposive sampling. Data analysis technique used is an interactive analysis technique that includes four stages, namely: (1) data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusions. The results of this study indicate that in the drama script Senja dengan Dua Kelelawar by Kirdjomulyo uses grammatical and lexical aspects to analyze textually. The use of analysis of grammatical and lexical aspects is precisely able to form a discourse that has cohesive forms. The unified form of drama script discourse is supported by grammatical aspects, namely reference, restoration, absorption, and sequencing. In grammatical aspects, it is dominated by reference. Persona referencing that is often used is single persona referencing, both my free form, mine, my left sticky form, and my right sticky form. Harmony of meaning is also supported by lexical aspects, namely repetition, synonymy, antonymy, collocation, hyponymy, and equivalence.